Handbook of amygdala structure and function - Urban, Janice H.; Rosenkranz, J. Amiel (Handbook of behavioral neuroscience, 2020)
Handbook of Amygdala Structure and Function, Volume 26, provides an updated overview on the functional neuroanatomy of amygdala nuclei, with an emphasis on interconnections (basolateral, central amygdala, medial amygdala) and their integration into related networks/circuits (prefrontal cortex, bed nucleus, nucleus accumbens). The design of this volume builds upon the foundations of functional neural circuits and the corresponding (cellular) electrophysiology important for the homeostatic control of amygdala function. This volume contains a dedicated section on the anatomical organization of the amygdala nuclei, emphasizing the role of neurotransmitters and neuropeptides that integrate signals and regulate behavior. Additional chapters discuss cellular physiology, plasticity and the integration of electrical signals that contribute to neural activity. The final section of the book connects the role of amygdala dysfunction and the development of disorders in human health and disease. Emphasizes a comparative and multidisciplinary approach on the topic of the amygdala Discusses, in detail, the role of amygdala dysfunction and the development of disorders in human health and disease Examines the current state of research in cellular physiology, plasticity and the integration of electrical signals Includes a dedicated section on neuropeptides, neurotransmitters and cannabinoids that links to behavior control.